1979
DOI: 10.1111/j.1748-5827.1979.tb06751.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and radiological features associated with spinal tumours in thirty dogs

Abstract: The clinical, neurological and radiographic features of thirty dogs with spinal tumours are described. Twenty were investigated at post mortem, and of these, eleven had primary nerve tissue tumours, four primary vertebral tumours, and in the remaining five the spinal involvement was secondary from neoplasms elsewhere in the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…Only 5% of secondary tumors in humans are diagnosed antemortem, and affected patients present more acutely and progress more rapidly than patients with primary tumors . Clinical progression in previous veterinary reports ranged from 1 to 504 days (mean, 55.7 days; median, 21 days) . Our data also indicated a variable clinical course.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Only 5% of secondary tumors in humans are diagnosed antemortem, and affected patients present more acutely and progress more rapidly than patients with primary tumors . Clinical progression in previous veterinary reports ranged from 1 to 504 days (mean, 55.7 days; median, 21 days) . Our data also indicated a variable clinical course.…”
Section: Discussionsupporting
confidence: 49%
“…Fifty‐six intramedullary spinal cord tumors have been reported in the veterinary literature . Primary tumors were documented in 41 cases and secondary tumors in 15 cases . The mean age, recorded for 49/55 cases, was 4.7 years.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of previous cases and those included in the present report provides interesting comparisons. Boxers were the breed most overrepresented in this study and were the most frequently affected breed in previous studies (4 of the 36 cases for which breed was reported) 5,7,9–12,14–19,33,35,36,39,40 . This may be a reflection of breed popularity or may represent the propensity of this breed to develop neoplasms.…”
Section: Discussionmentioning
confidence: 60%
“…4 METASTASIS IN THE DOG 209 then 1.0 mg/kg every other day for 14 days, and finally 0.5 mg/kg every other day). Eighteen days after discharge, the owner reported the dog was ambulatory, but had regressed when prednisone was decreased to 1 .O mg/kg every other day. Prednisone dose was increased to 1.0 mg/kg every 12 hours with instructions to slowly taper the dose.…”
Section: Dogmentioning
confidence: 99%